Effects of neonatal fentanyl on late adolescent opioid-mediated behavior - Crawford, Cynthia A.; Taylor, Jordan A.; Park, Ginny I.; Rios, Jasmine W.; Bunch, Joseph; Greenwood, Constance J.; Lopez Sanchez, David Y.; Gonzales, Diego J. (Frontiers in Neuroscience, 2023)
Introduction Because of the steady increase in the use of synthetic opioids in women of childbearing age, a large number of children are at risk of exposure to these drugs prenatally or postnatally through breast milk. While there is older literature looking at the effects of morphine and heroin, there are relatively few studies looking at the long-term effects of high-potency synthetic opioid compounds like fentanyl. Thus, in the present study, we assessed whether brief exposure to fentanyl in male and female rat pups during a period roughly equivalent to the third trimester of CNS development altered adolescent oral fentanyl self-administration and opioid-mediated thermal antinociception. Methods We treated the rats with fentanyl (0, 10, or 100 μg/kg sc) from postnatal day (PD) 4 to PD 9. The fentanyl was administered daily in two injections given 6 h apart. After the last injection on PD 9, the rat pups were left alone until either PD 40 where they began fentanyl self-administration training or PD 60 where they were tested for morphine- (0, 1.25, 2.5, 5, or 10 mg/kg) or U50,488- (0, 2.5, 5, 10, or 20 mg/kg) induced thermal antinociception. Results In the self-administration study, we found that female rats had more active nose pokes than male rats when receiving a fentanyl reward but not sucrose alone solution. Early neonatal fentanyl exposure did not significantly alter fentanyl intake or nose-poke response. In contrast, early fentanyl exposure did alter thermal antinociception in both male and female rats. Specifically, fentanyl (10 μg/kg) pre-treatment increased baseline paw-lick latencies, and the higher dose of fentanyl (100 μg/kg) reduced morphine-induced paw-lick latencies. Fentanyl pre-treatment did not alter U50,488-mediated thermal antinociception. Conclusions Although our exposure model is not reflective of typical human fentanyl use during pregnancy, our study does illustrate that even brief exposure to fentanyl during early development can have long-lasting effects on mu-opioid-mediated behavior. Moreover, our data suggest that females may be more susceptible to fentanyl abuse than males.